Comparison of the effects of Duphaston and Cetrotide on oocyte and embryo quality in women undergoing ICSI: A cross-sectional study - Niloofar Motaref; Sheyda Jouhari; Afsaneh Mohammadzadeh; Somaieh Kazemnejad; Narges Madadi; Sadaf Eghtedari; Abolfazl Ghoodjani (International Journal of Reproductive BioMedicine, 2020)
Background: Premature luteinizing hormone (LH) surge is one of the causes for assisted reproductive technology cycle cancellation, and it is needed to find novel approaches with improved efficacy and safety profile. Objective: To compare the effects of Duphaston and Cetrotide on the prevention of premature LH surge and characteristics of retrieved follicles and embryos in women undergoing intracytoplasmic sperm injection. Materials and Methods: In this retrospective cross-sectional study, 200 patients who were administrated recombinant follicle-stimulating hormone from the third day of menstruation cycle were included. When the follicular diameter reached above 13-14 mm, Cetrotide was prescribed in the control group, while in the case group, Duphaston was taken orally from the third day of cycle. The retrieved oocytes were fertilized in vitro by intracytoplasmic sperm. The level of hormones on the third day of menstruation and the characteristic of follicles, oocytes, and embryos were compared between the two groups. Results: Duphaston successfully inhibits premature LH surge. There was no significant difference in the level of follicle-stimulating hormone, estradiol, and LH between the case and control groups (p